Discovery of RNA-binding proteins and characterization of their dynamic responses by enhanced RNA interactome capture - Joel I. Perez-Perri (Nature Portfolio, 2018)
RNA interactome capture allows the detailed investigation of RNA-bound proteomes. Here the authors describe enhanced RNA-interactome capture using LNA-modified probes for increased sensitivity and specificity.